1994
DOI: 10.1159/000106741
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Alzheimer's Disease in Japan – Significance of Life-Styles

Abstract: A case-control study of Alzheimer''s disease was conducted in Japan; it involved 60 cases matched for sex and age with two resident controls each. Life-style was particularly highlighted in this study. Among many factors, 5 were accepted as significant risk factors: psychosocial inactivity, physical inactivity, head injury, loss of teeth and low education. A multiple logistic model was applied in order to evaluate synergism of major factors. Compared with those who have none of the factors, those who have all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
2
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 2 publications
8
132
2
5
Order By: Relevance
“…Certainly premorbid decline can cause reduction in activities in years preceding onset of clinical dementia, as demonstrated by Fabrigoule et al (20) in an incidence study of dementia in subjects who were followed for 3 years. This premorbid effect could influence relationships with physical (33), mental (32,34), and social activities (19). A study by Zabar and colleagues † † found no difference in activities between caseand highly selected control-group members participating in the Baltimore Longitudinal Study of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly premorbid decline can cause reduction in activities in years preceding onset of clinical dementia, as demonstrated by Fabrigoule et al (20) in an incidence study of dementia in subjects who were followed for 3 years. This premorbid effect could influence relationships with physical (33), mental (32,34), and social activities (19). A study by Zabar and colleagues † † found no difference in activities between caseand highly selected control-group members participating in the Baltimore Longitudinal Study of aging.…”
Section: Discussionmentioning
confidence: 99%
“…There was little more influence to give body activity by men than in the case of women. Kondoh et al (1995) conducted a survey on the remaining teeth in the aged and reported that the loss of teeth is related to the progression of dementia. It has also been reported that the loss of teeth is a risk factor for senile Alzheimer's dementia.…”
Section: Discussionmentioning
confidence: 99%
“…58 Tooth loss is also suggested to be a risk factor of Alzheimer's disease. Having no teeth, together with a lack of mental and physical activity, poor education, and previous head injuries, very greatly increases the probability of falling ill. 59 In these pathologies, hearing defects may likely be connected with poor results in speech audiometry.…”
Section: Dental Pathologies and Hearingmentioning
confidence: 99%